Soldados, armas y batallas en los grafitos históricos - Polo Lomero, L. Alberto,; Vinuales Ferreiro, Gonzalo,; Reyes Téllez, Francisco, (Archaeopress Archaeology, 2023)
This edited volume deals with the presence and representation of the military in historical graffiti and also those military enclaves that tell us their history through their graffiti. The backbone of this publication is the study of various sets of historical military-themed graffiti (representations of battles, armaments, infrastructure, warriors and soldiers, slogans or proclamations, etc.), all of them drawings and/or messages engraved in spaces linked to defence culture (the walls of castles, barracks, sentry boxes, prisons or bunkers, among others). The compendium of collected chapters presents us with a holistic and multi-temporal vision from the ancient world to contemporary times; from Pompeii to America, and with a particular focus on the Iberian Peninsula.